Nahdlatul Turats: The Islamic Philology Movement in Tracing the Scholarly Network of Nusantara Scholars - Sampurno, Margo (Muttaqien; Indonesian Journal of Multidiciplinary Islamic Studies, 2024)
This article examines the phenomenon of the revival of Islamic philology in Indonesia with the presence of Nahdlatul Turats. This was initiated by the exhibition of Syhaikhona Kholil Bangkalan’s work, namely Lajnah Turats. The concept of philology in tracing the ancient manuscript works of Nusantara scholars is done contextually with subjective and objective approaches. Data collection methods with documentation and analysis methods with descriptive-analytic. The results showed that the study of Islamic philology in Indonesia with the emergence of the Nahdlatul Turats movement has the potential for the revival of Islam in Indonesia which has indicators for the transformation of classical science in the present era. The process of revealing the scientific transmission network of Nusantara scholars can also be traced in depth through the works of books or manuscripts written. Analysis of Ibn Kholdun’s Ashabiyah theory in reviewing the Nahdlatul Turats movement in social solidarity can build a civilization through the spirit of mutual cooperation.